1120. Descriptive Analysis of Monoclonal Antibody Administration for Pregnant Patients with SARS-CoV-2 Infection. (15th December 2022) - Vikraman, Praveen Kumar; Chang, Kai Ming; Doan, Thien-Ly; Donaghy, Henry
Abstract: Background: We studied the safety and efficacy of the use of monoclonal antibodies (MAB) against SARS-CoV-2 in pregnant women who developed COVID-19 infection. Methods: We conducted a cross-sectional descriptive multi-center study of pregnant patients who developed SARS-CoV-2 infection from January 2021 to January 2022 and received MAB therapy. Primary outcomes assessed were infusion-related adverse events and pregnancy outcomes within one month of MAB infusion. The secondary outcomes assessed were hospitalization and ICU admission for COVID19 infection and thirty-day all-cause mortality. Results: 141 patients were included in the study (median age 33 +/- 5.3 SD, median BMI 28.9 +/- 8.42 SD). In terms of COVID vaccination status, 49.6% received one dose, 36.1% were fully vaccinated, and 7% received the booster dose. Most patients received casirivimab/imdevimab (105, 74.5%) followed by sotrovimab (33, 23.4%). Four patients developed adverse reactions to MAB infusion (two grade-2 reactions and two grade-1 reactions as per the National cancer institute infusion reaction grading criteria). Only one patient (0.7%) was hospitalized for COVID-19 infection, however, she was not hypoxic nor required ICU admission. Five patients delivered within four weeks of MAB administration, however, four of those patients were of gestational age > 37 weeks. Data for 30-day all-cause mortality was available on 88.7% (125) of the patients and data for 30-day pregnancy adverse outcomes was available on 86.5% (122) of the patients due to lack of follow-up within the Health System. There was no reported 30-Day all-cause mortality within the cohort. Two patients (1.4%) had premature rupture of the membrane and one patient (0.7%) had premature delivery within 30 days of receiving MAB. Two patients had preeclampsia (1.4%) and one patient (0.7%) was admitted for evaluations of decreased fetal movements. Conclusion: Administration of monoclonal antibodies against SARS-CoV-2 was well tolerated during pregnancy. Only 4 out of 141 (2.8%) had mild to moderate infusion-related reactions. The 30-day pregnancy adverse outcomes observed were well below the mean background rate. There was no reported mortality among MAB recipients and only one patient was hospitalized for mild COVID19 infection. Disclosures: All Authors : No reported disclosures.